MENTAL ILLNESS: BRAVERY IN THE FACE OF ADVERSITY - Hill, James (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2021)
Until recently, sufferers of mental health conditions faced not only the stigma attached to their illness but a critical lack of support in many Australian workplaces. Author James Hill has experienced the debilitating effects of severe mental illness. While fortunate to finally receive the help that allowed him to embark on a journey of recovery and return to employment, he quickly recognized the myriad of challenges that face mental health sufferers in the workplace, particularly in traditionally male-dominated industries. This narrative explores how the author has drawn upon his own experience to become a mental health advocate, working to create a blueprint for reform around workplace mental health. The paper follows how workplace programs of peer support have been successfully initiated, moreover, how a lived experience lens has been able to redefine workplace strategies and effectively deliver suicide prevention training and mental health education. By subverting conventional notions of masculinity and suffering that have long contributed to the epidemic of male suicides, the author continues to create realistic and sustainable change by openly using personal experiences to combat the stigma which shrouds the topic.